Two new species of Homidia (Collembola: Entomobryidae) from Southwestern China - Ma, Yi-Tong; Pan, Zhi-Xiang (Zootaxa, 2017)
Two new species of Homidia are described here. Homidia nigrifascia sp. nov. is characterised by dark pigment on Abd. II−III and posterior part of Abd. IV. Homidia obliquistria sp. nov. can be identified by its colour pattern, chaetae on ventral side of head and many macrochaetae on Abd. IV. Illustrations are provided for both new species. This is the first report of Homidia from Guizhou Province, China.